Pengaruh Social Media Marketing, Brand Ambassador Jkt48 Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Fashion Erigo Di Surakarta (Survei Pada Fanbase Jkt48 Di Surakarta) - Novita Mahastri , Amadea; Susanti, Retno (Teewan Journal Solutions, 2025)
This research aims to analyze the significance of the influence of social media marketing, brand ambassadors and product quality on purchasing decisions for Erigo fashion products in Surakarta. The type of data used is quantitative data. The data source used is primary data. The sampling technique used was non- probability sampling and purposive sampling with a total of 100. The data collection technique in this research used a questionnaire. Test the instrument using validity tests and reliability tests. The classical assumption test uses tests: multicollinearity, heteroscedasticity, autocorrelation and normality. Data analysis techniques use multiple linear regression tests, t tests, F tests and R².The results of the validity and reliability tests show that all statements regarding social media marketing, brand ambassadors and product quality are declared valid because the p value < 0.05 and reliable because Cronbach's alpha> 60. The results of the classical assumption test show that all variables have passed the multicollinearity and heteroscedasticity tests. , autocorrelation and normal distribution. The results of the regression analysis obtained the equation Y= 1.328 + 0.430 X1 + 0.112 X2 + 446 X3. The results of the t test showed that there was a significant influence of social media marketing (X₁), brand ambassador (X₂) and product quality (X₃) on purchasing decisions for Erigo fashion products in Surakarta. The results of the F test showed that the regression model used in this research was correct. The R² test results show that the contribution of the independent variable to the dependent variable is 76%, the remaining 23.5%.